Interpretasi Makna ‘Nikah’ dan Implikasinya Terhadap Hukum Perkawinan Perempuan dengan Ayah dari Pasangan Zinanya; Analisis Madzhab Fikih - Aspandi Aspandi (Indonesian Journal of Humanities and Social Sciences, 2023)
Different interpretations of the meaning of the word 'nikah' in the Qur'an and Hadith have implications for the law of marriage for women with the father of their adulterous partner. This study aims to determine the different interpretations of the meaning of marriage in the Qur'an and Hadith and its legal implications according to the schools of jurisprudence. This research method uses a normative juridical approach by examining the books of jurisprudence as the main legal material. With the literature study method, the primary data source of this research is in the form of documents of jurisprudence books related to the topic of discussion and secondary data sources in the form of research results, journals and other documents related to the research topic. The results of this study stated that there are three different interpretations of the jurisprudence Madzhab on the meaning of marriage in the Quran and Hadith. This difference in interpretation of the meaning of the word marriage has implications for the marriage law for women with the father of their adulterous partner. Mahdab Hanafi is of the view that a woman who commits adultery with someone has legal implications that she is haram to marry her father or the son of her adulterous partner. This view is different from the Shafi'i Madzhab which states otherwise.